Brand Capital and Stock Price Crash Risk - Hasan, Mostafa Monzur; Taylor, Grantley; Richardson, Grant (Management Science, 2022)
We examine the relationship between brand capital and stock price crash risk. Crash risk, defined as the negative skewness in the distribution of returns for individual stocks, captures asymmetry in risk, and has important implications for investment choices and risk management. Using a sample of 39,685 publicly listed U.S. firm-year observations covering 1975 to 2018, we show that brand capital is significantly and negatively related to crash risk. We also use an advanced machine learning approach and confirm that brand capital is a strong predictor of future stock price crashes. Our cross-sectional analyses show that this negative relationship is more evident for subsamples with transitory poor earnings performance or persistent good earnings performance, greater corporate tax avoidance, and weak corporate governance structures. The results survive numerous robustness tests, including the use of alternative measures of brand capital, crash risk, and several endogeneity tests. In sum, our findings are consistent with agency theory, suggesting that high levels of brand capital expose firms to investor and customer scrutiny, which reduces managerial opportunistic behavior that may include the accumulation and concealment of negative information. This paper was accepted by Karl Diether, finance.